Incorporación de extracto vegetal de Acelga (beta vulgaris subsp. vulgaris) y cultivos iniciadores fermentativos como reemplazo de nitratos para la elaboración de Pepperoni. - Bedón Almache, Dennis Steeve (2018)
The aim of the research was to elaborate meat cured/mature sausage type pepperoni based on the incorporation of swiss chard in powder and the action of starter crops for meat products, that contain two types of bacteria (Pediococcus acidilactici and Pediococcus pentosaceus) as replacement of nitrate salts that are used on meat cured products. This investigation was generated due to the problematic facing industry since 2005 where the World Health Organization (WHO) mentions that: "The excessive consumption of nitrate salts it causes digestive problems and probably stomach cancer". The research was carried out on the laboratories of Meat Industry belonging Agroindustrial Engineering Career. Nine treatments were performed combined swiss chard powder in the following concentrations in 0,15%; 0,25% and 0,35% concentrations plus the started cultures in proportions of 0,010 %; 0,020 % and 0,030%. The best treatment decided by performed result of microbiological quantifications sensory analysis. The microbiological was analyses were performed in the laboratory of food analysis "LABOLAB" located on Quito. The best treatment was t8; containing less number of microbial load of forming units of colony per gram (UFC/g) of Escherichia Coli and Salmonella. t8 presented major acceptability to the tasters. Additionality t8 was conducted analysis of residual nitrite and microbiological of Clostridium perfringens ufc/g y Staphylococcus aureus ufc/g to the t8. The yield of the final product of the best treatment was 65,93%, due to the loss of weight that was generated during the fermentation and ripeness. The cost of the best treatment was $2,65 in a presentation of 100g. It can be concluded that the product does not present health risk to the consumer and accessible purchase to commercial pepperoni.